Availability of Aftercare for Youth Departing Group Homes. Issue 3 (1st October 2016) - Tyler, Patrick M.; Thompson, Ronald W.; Trout, Alexandra L.; Lambert, Matthew C.; Synhorst, Lori L.
ABSTRACT: Aftercare has been suggested to improve the outcomes of youth who depart group homes. This project used a survey method to collect data from 38 agency leaders from across the United States on the aftercare supports they believed were available for youth departing group homes and returning to their homes/schools prior to high school graduation. The results revealed that 34% of agencies provided an aftercare service with a model, and 29% of agencies received external funding for aftercare. The findings are summarized and limitations and implications for future research are discussed.